Bronchial wall necrosis secondary to mucormycosis following SARS-Cov2 infection: A case report - Ghazal Arjmand; Elham Askari, MD; Arya Kazemi; Ehsan Zarei, MD; Sara Haseli, MD; Nazanin Sadraei, MD (Radiology Case Reports, 2022)
Coronavirus 2019 infection (COVID-19) has a broad spectrum of clinical complications, some unrecognized. Herein, a case of a diabetic patient with multiple episodes of hemoptysis 2 months following her recovery from SARS-CoV-2 infection is reported. The initial computed tomography (CT scan) revealed the left lower lobe collapsed secondary to bronchial narrowing and obliteration. Bronchoscopy was performed, indicating necrotic endobronchial tissue, which was confirmed histopathologically as invasive mucormycosis. Bronchial necrosis due to mucormycosis is an unusual presentation of COVID-19-associated pulmonary mucormycosis. The accurate diagnosis could be challenging as it can resemble other pathologies such as malignancies. Therefore, it is crucial to identify this fatal complication in patients with prolonged COVID-19 and lung collapse.